PENGARUH MOTIVASI BELAJAR TERHADAP PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PROBLEM BASED LEARNING - Dinda Safrima Sekar Kinanthi; Nelly Fitriani; Puji Nurfauziah (IKIP Siliwangi, 2022)
The Covid-19 pandemic has led to distance learning (PJJ). This results in a lack of student motivation which leads to a decrease in learning outcomes. This study aims to increase students' learning motivation in the form of providing motivational videos. This study used purposive sampling with 10 students of class VII-B at SMPN 1 Margaasih. The researcher also uses Kemmis and Taggart's research model and the data collection technique used is the Likert Scale Technique. The analytical technique used is by distributing a learning motivation questionnaire. After being given a motivational video, learning outcomes are directly proportional to the results of learning motivation. With the results of the research Cycle 1 is 40%, Cycle 2 is 80%, and Cycle 3 is 100%. From this research, the researcher concludes that learning motivation affects learning outcomes.